The Moderating Effect of Earnings Management on The Relationship Between CEO Narcissism And Tax Aggressiveness - Khadijah Darwin; Amiruddin Amiruddin; Syarifuddin Syarifuddin; Darmawati Darmawati; Rahmawati Hs (Al-Buhuts, 2024)
This study aims to test and find the effect of earnings management acting as moderating variable on the relationship between CEO Narcissism and tax aggressiveness. 14 mining companies in Indonesia became sample in this research, with five years of observation for a total of 70 observations. The nexus between variables was analyses using Moderated Regression Analysis (MRA) where this research variable consists of tax aggressiveness, CEO narcissism, while earnings management is moderating variable. The results found that a moderating effect was found on the relationship between CEO narcissism and tax aggressiveness. This indicates that an improved business performance will encourage companies to carry out proactive financial management. Corporate governance can reduce the impact of aggressive tax-based earnings management